Mechanisms of Vascular Inflammation and Potential Therapeutic Targets: A Position Paper From the ESH Working Group on Small Arteries - Jimenez Rios, Francisco J.; de Ciuceis, Carolina; Georgiopoulos, Georgios; Lazaridis, Antonios; Nosalski, Ryszard; Pavlidis, George; Tual-Chalot, Simon; Agabiti-Rosei, Claudia; Camargo, Livia L.; Dąbrowska, Edyta; Quarti-Trevano, Fosca; Hellmann, Marcin; et al. (Hypertension, 2024)
Inflammatory responses in small vessels play an important role in the development of cardiovascular diseases, including hypertension, stroke, and small vessel disease. This involves various complex molecular processes including oxidative stress, inflammasome activation, immune-mediated responses, and protein misfolding, which together contribute to microvascular damage. In addition, epigenetic factors, including DNA methylation, histone modifications, and microRNAs influence vascular inflammation and injury. These phenomena may be acquired during the aging process or due to environmental factors. Activation of proinflammatory signaling pathways and molecular events induce low-grade and chronic inflammation with consequent cardiovascular damage. Identifying mechanism-specific targets might provide opportunities in the development of novel therapeutic approaches. Monoclonal antibodies targeting inflammatory cytokines and epigenetic drugs, show promise in reducing microvascular inflammation and associated cardiovascular diseases. In this article, we provide a comprehensive discussion of the complex mechanisms underlying microvascular inflammation and offer insights into innovative therapeutic strategies that may ameliorate vascular injury in cardiovascular disease.